COURSE THEORY AS THE BASIS OF THE EXCHANGE RATE POLICY - Швець, Наталія; Полагнин, Дмитро (Socio-economic relations in the digital society, 2019)
The problems of determining the optimal exchange rate and forecasting its impact on economic processes require the search for new approaches to the study of fundamental and applied exchange rate models in the sphere of influence of various interests of economic relations. The exchange rate theory examines the value problems of the currency, the dependence of currencies on the balance of payments and its dynamics, which gives some insight into the processes of currency exchange. The practical function of exchange rate theory is to choose or develop methods of adjusting the exchange rate, depending on the economic situation in the market. Issues of conflicts of interest of exporters who wish to use exchange rate instruments to increase profits and interests of other economic entities that, on the contrary, require self-regulation of the exchange rate, have some political color. The main purpose of the conceptual framework of the exchange rate policy is to form an optimal exchange rate to ensure price stability, financial security of the country and the well-being of the population. Therefore, it is necessary to seek a compromise in resolving such confrontations. From a methodological point of view, different approaches can be used to study exchange rate theories in the course of the exchange rate policy. The article discusses political and empirical approaches to the use of exchange rate theories. The advantages and disadvantages of each approach and its impact on exchange rate policy are outlined. The theoretical models of exchange rate formation, its forecasting in the short and long periods are described. Separately, there are generations of models that explain the currency crises. The problems of research of course formation in the context of emergence of mutually exclusive ideas are defined. It is proved that in practice those approaches to exchange rate formation that are formed under certain economic policy goals and implemented according to conditions and interests can be implemented. Further consideration is required to explore the relationship between a country’s tactical or strategic economic policy goals and the interests of economic entities in the exchange rate equilibrium model.
Keywords: theory; model; exchange rate; exchange rate policy; political approach; empirical approach